FRI0152 Inflammasomes activation occurs in the inflamed tissues of as patients and drives il-23 expression. (12th June 2018) - Ciccia, F.; Rizzo, A.; Guggino, G.; Alessandro, R.; Raimondo, S.; Macaluso, F.; Peralta, S.; Milling, S.; Elewaut, D.
Abstract : Background: A growing body of evidences indicate that the aberrant activation of innate immune systems, occurring in genetically predisposed patients, drives inflammatory processes in Ankylosing Spondylitis (AS). 1 Objectives: Aim of this study was to evaluate the activation and the functional relevance of inflammasome pathways in patients with AS. Methods: Intestinal, synovial and bone marrow expression of inflammasome pathways, pyroptosis and IL-1b and IL-18 was evaluated in AS patients. Organic acid extraction was performed on ileal samples as previously described on. 2 The expression of the metabolite-sensing receptors GPR43 and GPR109A involved in the regulation of the intestinal inflammasome was also assessed. The role of intestinal dysbiosis in modulating inflammasome activation was also studied in AS patients and HLA-B27 transgenic rats. Inflammasome activation was evaluated in isolated peripheral AS monocytes. The role of LPS, PGE2 and nicotine in inducing monocyte inflammasome activation and the role of inflammasome in modulating IL-23 production was also evaluated. Results: Activation of inflammasomes was observed in the inflamed gut, synovial and bone marrow samples of AS patients and associated with an increased expression of caspase-1, IL-1b and IL-18. In AS, AIM2 expression was observed in the context of tuft cells and of adherent ileal bacteria. Inflammasome activation in AS gut, was associated with the occurrence of dysbiosis and increased pyroptosis as demonstrated by the membrane localization of Gasdermin D. Isolated intestinal bacteria from AS ileal samples, significantly modulated inflammasome activation in isolated monocytes. Reduced Short-chain fatty acids concentrations and increased expression of GPR43 and GPR109 were demonstrated in the AS ileal samples. Inflammasome activation was also observed in the inflamed gut of HLA-B27 TG rats and suppressed by antibiotics treatment. Increased expression of NLRP3, NLRC4 and AIM2 was confirmed in AS isolated peripheral monocytes. Serum levels of IL-1b and IL-18 were increased in AS patients, especially in smoker patients, and directly correlated with the ASDAS-CRP. In in vitro studies, LPS and nicotine strongly activated NLRP3, NLRC4 and AIM2 pathways in AS monocytes. The CC genotype of PTGER4 SNP rs6896969 was associated with a significantly increased activation of inflammasome in AS. Finally, inflammasome activation in AS monocytes was required for the induction of IL-23p19 expression in an IL-1b-dependent way. Conclusions: Inflammasome activation occurs in AS patients being modulated by a plethora of different stimuli. Inflammasome drives IL-23 production in an IL-1b-dependent mechanism in AS patients supporting the auto-inflammatory nature of the disease and possibly representing a future therapeutic target in AS. References: [1] Ciccia F, et al. Intestinal dysbiosis and innate immune responses in axial spondyloarthritis. Curr Opin Rheumatol2016. [2] Fuller M, et al. The short chain fatty acid receptor, FFA2, contributes to gestional glucose homeostasis. American Journal of Physiology – Endocrinology and Metabolism2015. [3] Macia L, et al. Metabolite-sensing receptors GPR43 and GPR109 facilitate dietary fibre-induced gut homeostasis through the regulation of the inflammasome. Nat Commun2015. Disclosure of Interest: None declared